In vitro cellular interaction of drug-loaded liposomes with 2D and 3D cell culture of U87-MG cell line - Tasneem Alsheleh; Manar Zraikat; Fadwa Daoud; Dana A. Alqudah; Sharif Abdelghany; Ahmed Abu Siniyeh; Walhan Alshaer (PLoS ONE, 2025)
The distinctive physiological and physical properties of 3D cultures that mimic tumor microenvironments in vivo make them more suitable for assessing the efficacy of drugs and nanoparticles compared to 2D culture models. Therefore, this study aims to examine and contrast how liposomes interact with cell cultures in both 2D and 3D models. Hanging drop technique was used to generate 3D spheroids. Cellular toxicity of Doxorubicin and Doxil®-liposomes was tested using an MTT assay. Cellular uptake of Doxil®-liposomes was investigated in 3D and 2D cell culture models using flow cytometry and confocal microscopy. Finally, migration and invasion assays were used to investigate the Doxil®-liposomes interaction with the two models 2D model and 3D model, respectively. Our findings show that cells were able to form spheroid structures when a specific cell ratio was maintained. Flow cytometry analysis revealed that 2D cells exhibited higher Doxil®-liposome uptake than 3D cells. The data obtained from confocal and fluorescent microscopy supported the findings of the flow cytometry analysis. Furthermore, the MTT assay showed that Doxil®-liposomes induced less metabolic-disruption compared to free Doxorubicin. Our results also demonstrated that Doxil®-liposomes interacted more loosely with the 3D model than 2D cells, which was further confirmed by measurements of the total migration and invasion areas. Therefore, a 3D model replicating the in vivo conditions of tumor structure and extracellular matrix to assess the delivery of liposomal-nanoparticles to spheroids through a collagen matrix can be more informative and recapitulate the in vivo microenvironment than the 2D model.